A Research Program for Studying LAMs and Community in the Digital Age - Vårheim, Andreas; Skare, Roswitha; Lenstra, Noah; Latham, Kiersten F.; Grenersen, Geir (Proceedings from the Document Academy, 2018)
The paper outlines a research effort into the changing representations, policies, strategies, activities, and practices of libraries, archives, and museums (LAMs) in the digital age. Comprehensive social changes including big slow-moving processes, such as aging populations, global migration, technological change, and environmental change, expose communities and LAM institutions to vulnerabilities. How do the institutions handle vulnerabilities, how do they become more resilient, and how do they contribute to building the resilience of their local communities?